Study on quality changes of Idesia polycarpa oil during high-temperature cooking - Hongxia Feng; Shuwen Zheng; Mingfa Song; Fangyu Fan; Yunhe Chang; Juncai Hou (CyTA - Journal of Food)
Idesia polycarpa oil, an emerging woody oil rich in linoleic acid (>82%), remains understudied for its high-temperature stability despite its nutritional promise. This study aimed to evaluate the high-temperature cooking performance of I. polycarpa oil. Deep-frying, pan-frying, and stir-frying experiments with potatoes used I. polycarpa oil, soybean oil, and rapeseed oil. The oils were comprehensively assessed by measuring indices like acid value, peroxide value, anisidine value, conjugated dienes and trienes, polar compounds, and trans-fatty acids. Results showed that during deep-frying, the changes in various physical and chemical indicators of I. polycarpa oil, such as the increase in acid value, were 30.16%; the anisidine value increased by 85.46; the increment of polar compounds of I. polycarpa oil (19.07%) was lower than that of soybean oil (27.13%) and rapeseed oil (32.53%). Its trans-fatty acid content was consistently the lowest. These findings validate I. polycarpa oil as a thermally stable alternative for high-temperature culinary applications.